The Role of Standardization of Goods in the Context of Protecting the Interests of Car Spare Part Consumers in Pekanbaru - Silmia Dahnil; Hayatul Ismi; Zulfikar Jayakusuma (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2024)
The purpose of this study is to determine the important role of standardization in various policies and public interests in controlling product quality, especially regarding the standardization of car spare parts products in order to guarantee the interests and provide consumer protection for car users. This type of research is field legal research or sociological research. Data collection techniques in sociological legal research through interviews with related parties, distributing questionnaires, and literature studies. In drawing conclusions, the author uses a deductive thinking method, namely starting from a general proposition whose truth is already known (believed) and ending with a more specific conclusion (new knowledge). The implementation of SNI is basically voluntary, but in matters relating to interests, safety, and security, the ministry or authorized non-ministerial government agency can stipulate the mandatory implementation of SNI through a Ministerial Regulation or Regulation of the Head of a Non-ministerial Government Agency. In this regard, car spare parts are a very important component of a car. However, currently the regulation regarding the standardization of car spare parts, including in Pekanbaru City, has not been regulated by the relevant party, namely the government through the National Standardization Agency (BSN), even though standardization plays a very important role in protecting consumers.